Deconstructing the Infrastructure: A Complex History of Diachronous Metamorphism and Progressive Deformation during the Late Cretaceous to Eocene in the Thor-Odin–Pinnacles Area of Southeastern British Columbia - van Rooyen, Deanne; Carr, Sharon D. (Geoscience Canada, 2016)
The Thor-Odin dome is a basement-cored tectonothermal culmination in southern British Columbia containing high-grade metamorphic rocks that were polydeformed in the Late Cretaceous to Eocene. The rocks south of the Thor-Odin dome that extend ca. 20 km to the Pinnacles culmination and Whatshan batholith comprise a heterogeneous tract of polydeformed medium- to high-grade metamorphic rocks and host the South Fosthall pluton near the base of the structural section. They lie in the footwall of the Columbia River fault (CRF) zone, a moderately east-dipping, ductile-brittle, normal fault that was active after ca. 55 Ma and reactivated periodically up to 30 Ma. This tract of rocks has been interpreted as a mid-crustal zone that was exhumed and cooled during Eocene extension or, alternatively, a mid-crustal channel that was bounded at the top by the CRF and was active during the Late Cretaceous to Eocene. However, the timing of metamorphism, deformation, anatexis in basement rocks, and intrusion of leucogranite plutons reveals that there are four tectonothermal domains within the tract that each experienced metamorphism, deformation and cooling at different times. These rocks record Cretaceous metamorphism and cooling in the upper structural levels and three stages of progressive metamorphism and penetrative deformation that migrated into deeper crustal levels in the Paleocene and Eocene producing a complex structural section that was exhumed in part due to motion on the Columbia River fault zone, and in part due to NE-directed transport over a basement ramp. RÉSUMÉ Le dôme de Thor-Odin correspond à une culmination tectonothermique d’un noyau de socle dans le sud de la Colombie-Britannique renfermant des roches métamorphiques de haute intensité polydéformées entre le Crétacé supérieur et l’Éocène. Les roches au sud du dôme de Thor-Odin qui s’étendent sur environ 20 km jusqu’à la culmination des Pinnacles et du batholite de Whatshan sont constituées d’une bande hétérogène de roches polydéformées à faciès métamorphique d’intensité moyenne à élevée qui constitue l’encaissant du pluton de South Fosthall près de la base de la colonne structurale. Elles se trouvent dans l'éponte inférieure de la zone de faille de la rivière Columbia (CRF), une faille normale à pendage modéré vers l’est, ductile-fragile, qui a été active après 55 Ma environ et a été réactivée périodiquement jusqu'à 30 Ma. Cette bande de roches a été interprétée comme une zone de mi-croûte qui a été exhumée et a refroidi durant l’extension éocène ou alors comme un canal mi-crustal qui a été limité au sommet par la CRF, et qui a été actif de la fin du Crétacé jusqu’à l’Éocène. Toutefois, la chronologie du métamorphisme, de la déformation, de l’anatexie dans les roches du socle, et de l'intrusion de plutons de leucogranite, montre qu'il existe quatre domaines tectonothermiques pour chaque bande qui ont subit du métamorphisme, de la déformation et du refroidissement à différents moments. Ces roches exhibent un métamorphisme et un refroidissement crétacé dans les niveaux structuraux supérieurs et trois stades de métamorphisme progressif et de déformation pénétrative qui ont migré dans les niveaux crustaux profonds au Paléocène et à l’Eocène constituant ainsi une colonne structurale complexe qui a été exhumée en partie en raison du mouvement de la zone de faille de Columbia River, et en partie en raison du transport vers le N.-E. sur une rampe de socle.